The Toxicity Exerted by the Antibiotic Sulfadiazine on the Growth of Soil Bacterial Communities May Increase over Time - Vanesa Santás-Miguel (International Journal of Environmental Research and Public Health, 2020)
The toxicity exerted by the antibiotic sulfadiazine on the growth of soil bacterial communities was studied in two agricultural soils for a period of 100 days. In the short-term (2 days of incubation), the effect of sulfadiazine on bacterial growth was low (no inhibition or inhibition <32% for a dose of 2000 mg·kg−1). However, sulfadiazine toxicity increased with time, achieving values of 40% inhibition, affecting bacterial growth in both soils after 100 days of incubation. These results, which were here observed for the first time for any antibiotic in soil samples, suggest that long-term experiments would be required for performing an adequate antibiotics risk assessment, as short-term experiments may underestimate toxicity effects.